Native to designed: microbial α-amylases for industrial applications - Oslan, Siti Nurbaya; Lim, Si Jie (PeerJ, 2021)
Background. α-amylases catalyze the endo-hydrolysis of α-1,4-D-glycosidic bonds in starch into smaller moieties. While industrial processes are usually performed at harsh conditions, α-amylases from mainly the bacteria, fungi and yeasts are preferred for their stabilities (thermal, pH and oxidative) and specificities (substrate and product). Microbial α-amylases can be purified and characterized for industrial applications. While exploring novel enzymes with these properties in the nature is time-costly, the advancements in protein engineering techniques including rational design, directed evolution and others have privileged their modifications to exhibit industrially ideal traits. However, the commentary on the strategies and preferably mutated residues are lacking, hindering the design of new mutants especially for enhanced substrate specificity and oxidative stability. Thus, our review ensures wider accessibility of the previously reported experimental findings to facilitate the future engineering work. Survey methodology and objectives. A traditional review approach was taken to focus on the engineering of microbial α-amylases to enhance industrially favoured characteristics. The action mechanisms of α- and β-amylases were compared to avoid any bias in the research background. This review aimed to discuss the advances in modifying microbial α-amylases via protein engineering to achieve longer half-life in high temperature, improved resistance (acidic, alkaline and oxidative) and enhanced specificities (substrate and product). Captivating results were discussed in depth, including the extended half-life at 100 ◦C, pH 3.5 and 10, 1.8 M hydrogen peroxide as well as enhanced substrate (65.3%) and product (42.4%) specificities. These shed light to the future microbial α-amylase engineering in achieving paramount biochemical traits ameliorations to apt in the industries. Conclusions. Microbial α-amylases can be tailored for specific industrial applications through protein engineering (rational design and directed evolution). While the critical mutation points are dependent on respective enzymes, formation of disulfide bridge between cysteine residues after mutations is crucial for elevated thermostability. Amino acids conversion to basic residues was reported for enhanced acidic resistance while hydrophobic interaction resulted from mutated hydrophobic residues in carbohydrate binding module or surface-binding sites is pivotal for improved substrate specificity. Substitution of oxidation-prone methionine residues with non-polar residues increases the enzyme oxidative stability. Hence, this review provides conceptual advances for the future microbial α-amylases designs to exhibit industrially significant characteristics. However, more attention is needed to enhance substrate specificity and oxidative stability since they are least reported.